How autocrats subvert elections : resistance to Trump and Trumpism - Abel, Richard L. (Defending American democracy, 2025)
Chronicling and analyzing resistance to the threat that autocracy poses to American liberal democracy, this book provides the definitive account of the response to the January 6, 2021, assault on the Capitol and Republican efforts to overturn the 2020 election and bias future elections in their favor.In December 2020, Donald Trump invited supporters to DC for what he promised would be a "wild" demonstration against Biden's victory. On January 6, 2021, he directed the mob he had summoned to march on the Capitol, where it ransacked the building, caused five deaths and hundreds of injuries, and delayed but failed to prevent certification of the election. Although some Congressional Republicans briefly distanced themselves from Trump, the party quickly closed ranks around him. The business community, similarly, initially expressed criticism but soon resumed campaign contributions to Republicans. Democrats sought to impeach Trump (for the second time), but Republicans blocked conviction. Democrats created a House Select Committee, which exposed Trump's complicity through dramatic televised hearings and a comprehensive report. Republicans responded by denying there had been a riot-one calling it a mere tourist visit-and sanctifying those arrested. Nevertheless, all but two of the nearly 1,400 charged were convicted. Judges appointed by both Democratic and Republican presidents harshly condemned the insurrectionists, imposing sentences that did not vary by the judge's party preference. This book contextualizes these continuing threats to American democracy through an opening chapter exposing distressing parallels with the rise of Nazism in 1930s Germany. The penultimate chapter examines the ways in which Republicans persisted in seeking to overturn the 2020 election and distort subsequent elections by gerrymandering and creating obstructions to potential Democratic voters. All the chapters focus on the multiple forms of resistance-politics, social action, economic pressure, media exposure, and criminal prosecution-evaluating their relative efficacy and comparing them with modes of resistance analyzed in the author's related volumes.This definitive account and analysis of Trump's and his supporters' attempts to subvert the 2020 election will appeal to scholars, students, and others with interests in politics, populism, and the rule of law, and more specifically, to those concerned with resisting the threat that autocracy poses to liberal democracy.